Garments for functional electrical stimulation: Design and proofs of concept. (July 2019) - Moineau, Bastien; Marquez-Chin, Cesar; Alizadeh-Meghrazi, Milad; Popovic, Milos R
Introduction: Repeated use of functional electrical stimulation can promote functional recovery in individuals with neurological paralysis. We designed garments able to deliver functional electrical stimulation. Methods: Shirts and pants containing electrodes knitted with a conductive yarn were produced. Electrodes were moistened with water before use. Stimulation intensity at four thresholds levels (sensory, movement, full range of motion, and maximal), stimulation comfort, and electrical properties of the interface were tested in one able-bodied subject with garment electrodes and size-matched conventional gel electrodes. The pants and shirt were then used to explore usability and design limitations. Results: Compared to gel electrodes, fabric electrodes had a lower sensory threshold (on forearm muscles) but they had a higher maximal stimulation threshold (for all tested muscles). The stimulation delivery was comfortable when the garment electrodes were recently moistened; however, as the electrodes dried (within 9 to 18 min) stimulation became unpleasant. Inconsistent water content in the fabric electrodes caused inconsistent intensity thresholds and inconsistent voltage necessary to apply a desired stimulation current. Garments' tightness and impracticality of electrode lead necessitate further design improvement. Conclusions: Fabric electrodes offer a promising alternative to gel electrodes. Further work involving people with paralysis is required to overcome the identified challenges.